2021
DOI: 10.1155/2021/8867647
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Efficiency of Detailed Soil Resource Mapping on Transitional Volcanic Landforms Using a Geomorphometric Approach

Abstract: For developing countries, detailed soil resource data and maps are essential in land-use planning. Unfortunately, obtaining detailed soil data for mapping is expensive. Detailed soil studies and mapping in developing countries often use the grid method. In addition to being time-consuming, the grid method needs a lot of sample points and surveyors. Geomorphometry can be a less expensive alternative for detailed soil mapping. Geomorphometry uses computationally measured terrain characteristics to describe other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
3
0
1
Order By: Relevance
“…The results showed that the erosion processes were controlled by both physical characteristics of the land, such as the climate, especially the intensity of rain, topography, especially relief, vegetation, soil, and the human activities (Figure 3). Meanwhile, suspension flows derived from erosion in the channel occurred at the mountain watersheds with settlement land use triggered by the accumulation and concentration of streams that experience an increase in flow discharge (Sambodo & Arpornthip, 2021). Based on this study, natural processes following watershed characteristics and anthropogenic activities such as the type of land use in the volcano watershed area can trigger erosion and sources of suspension production that cause soil loss.…”
Section: The Characteristics Of the Grain Content Of The Suspension Flowmentioning
confidence: 86%
“…The results showed that the erosion processes were controlled by both physical characteristics of the land, such as the climate, especially the intensity of rain, topography, especially relief, vegetation, soil, and the human activities (Figure 3). Meanwhile, suspension flows derived from erosion in the channel occurred at the mountain watersheds with settlement land use triggered by the accumulation and concentration of streams that experience an increase in flow discharge (Sambodo & Arpornthip, 2021). Based on this study, natural processes following watershed characteristics and anthropogenic activities such as the type of land use in the volcano watershed area can trigger erosion and sources of suspension production that cause soil loss.…”
Section: The Characteristics Of the Grain Content Of The Suspension Flowmentioning
confidence: 86%
“…2 was used to generate the total erosion rate in the watershed key area at 1,657.94 ton/ha/yr. This study indicated that high flow rates were able to influence the sediment flow and erosion process in dryland agriculture areas, leading to soil loss (Sambodo & Arpornthip, 2021). The extent to the effect of flow discharge on the sediments is significantly dependent on erosion, particularly the soil erodibility (Morgan, 2005;Hadini et al, 2019).…”
Section: Calculation Of Sediment Discharge and Soil Lossmentioning
confidence: 95%
“…Lokasi yang menjadi area studi adalah Sub DAS Bompon di Kabupaten Magelang, Indonesia. Wilayah ini berada di area transisi antara Gunung Sumbing dan Pegunungan Menoreh yang sangat rawan erosi dan longsor (Sambodo & Arpornthip, 2021). Luaran dari penelitian ini adalah tahapan identifikasi indikator dan peta kerentanan fisik rumah terhadap longsor melalui interpretasi foto udara UAV.…”
Section: Metodeunclassified